2021
DOI: 10.1002/ldr.4085
|View full text |Cite
|
Sign up to set email alerts
|

Human–desertification coupling relationship in a karst region of China

Abstract: Forward and reverse succession of karst rocky desertification (KRD) occur simultaneously and are linked to human activity, thus presenting a mutual feedback loop.Previous studies have focused on the unilateral human-driven mechanism of KRD or KRD's impact on social-economic activities. These lack quantitative measurement and an in-depth understanding of the interactions involved. Therefore, this study builds and applies a novel model for measuring the coupling relationship and degree between KRD and social-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…It is concluded that ecological quality is generally negatively correlated with economic development, which is closely related to the past model of sacrificing ecological resources for economic development (Xu & Zhang, 2021). Among them, the trade-off between greening and the economy in non-degraded ecoregions is alleviated with the time of ERP.…”
Section: Potential Factors Affecting the Stability Of Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…It is concluded that ecological quality is generally negatively correlated with economic development, which is closely related to the past model of sacrificing ecological resources for economic development (Xu & Zhang, 2021). Among them, the trade-off between greening and the economy in non-degraded ecoregions is alleviated with the time of ERP.…”
Section: Potential Factors Affecting the Stability Of Resultsmentioning
confidence: 80%
“…Instead, it is exacerbated in degraded ecoregions. Generally, the economy is closely related to land development (Xu & Zhang, 2021). On the one hand, ERP in degraded ecoregion promotes land functional transformation and agricultural livelihood shift compared to developed land, which limits land development and economic development.…”
Section: Potential Factors Affecting the Stability Of Resultsmentioning
confidence: 99%
“…The third category was that the forest restoration tended to the areas with rich forest resources, while the native forest was not protected well, mainly in the karst area of Guizhou Province. The comprehensive rocky desertification control project in Guizhou Province had 78 pilot counties in 2008, covering the province's whole rocky desertification control region, and the afforestation was the main measure in this region (Xu & Zhang, 2021). The fourth was the category in which areas with rich forest resources were protected well, while the forest restoration was limited, mainly occurred in Chongqing City and the karst counties of Yunnan Province.…”
Section: Discussionmentioning
confidence: 99%
“…Some have studied the relationship between KRD, natural factors and socio‐economic factors (Xu & Zhang, 2014), while others have simulated the future evolution/trend of KRD (Chen et al, 2021; Xu & Zhang, 2018), and found that geological factors play the first role in determining the macro‐ecological pattern of KRD (Jiang et al, 2020). Restoration and reconstruction efforts in the area have helped to restore vegetation cover (Qi et al, 2013), and there has been a shift from negative coupling to positive coupling, then to a negative coupling between KRD and urbanization (Xu & Zhang, 2021). In some studies, the process of landscape transition in KMA, that is, the formation process of KRD has been emphasized (Jiang et al, 2014; Wang, Xin, & Wang, 2019; Wang, Zhang, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%